A case of synchronous triple autoimmune disorders secondary to thymoma: Pure red cell aplasia, Good's syndrome, and thymoma-associated multi-organ autoimmunity - Yuta Nakagawa; Kinnosuke Matsumoto; Makoto Yamamoto; Haruhiko Hirata; Takayuki Shiroyama; Kotaro Miyake; Yuji Yamamoto; Tomoki Kuge; Midori Yoneda; Yujiro Naito; Yasuhiko Suga; Kiyoharu Fukushima; et al. (Respiratory Medicine Case Reports, 2022)
Pure red cell aplasia (PRCA), Good's syndrome (GS), and thymoma-associated multiorgan autoimmunity (TAMA) are associated with thymoma. Herein, we describe the case of a 56-year-old woman with PRCA, GS, and TAMA simultaneously. She was treated with cyclosporine, immunoglobulin supplementation, and prednisolone; however, she died of uncontrolled sepsis due to extreme immunosuppression. The combination of these three diseases is likely to lead to fatal infections, and to avoid such infections, it may be necessary to reduce or discontinue immunosuppressants and steroids as soon as possible if the diseases are controlled, as well as regular immunoglobulin supplementation.